DNA as Tunable Adaptor for siRNA Polyplex Stabilization and Functionalization - Philipp Heissig; Philipp M. Klein; Philipp Hadwiger; Ernst Wagner (Elsevier, 2016)
siRNA and microRNA are promising therapeutic agents, which are engaged in a natural mechanism called RNA interference that modulates gene expression posttranscriptionally. For intracellular delivery of such nucleic acid triggers, we use sequence-defined cationic polymers manufactured through solid phase chemistry. They consist of an oligoethanamino amide core for siRNA complexation and optional domains for nanoparticle shielding and cell targeting. Due to the small size of siRNA, electrostatic complexes with polycations are less stable, and consequently intracellular delivery is less efficient. Here we use DNA oligomers as adaptors to increase size and charge of cargo siRNA, resulting in increased polyplex stability, which in turn boosts transfection efficiency. Extending a single siRNA with a 181-nucleotide DNA adaptor is sufficient to provide maximum gene silencing aided by cationic polymers. Interestingly, this simple strategy was far more effective than merging defined numbers (4-10) of siRNA units into one DNA scaffolded construct. For DNA attachment, the 3' end of the siRNA passenger strand was beneficial over the 5' end. The impact of the attachment site however was resolved by introducing bioreducible disulfides at the connection point. We also show that DNA adaptors provide the opportunity to readily link additional functional domains to siRNA. Exemplified by the covalent conjugation of the endosomolytic influenza peptide INF-7 to siRNA via a DNA backbone strand and complexing this construct with a targeting polymer, we could form a highly functional polyethylene glycol-shielded polyplex to downregulate a luciferase gene in folate receptor-positive cells.